Russell Body Duodenitis In A Patient With Duodenal Adenoma And High-Grade Dysplasia. (28th October 2020) - Sun, L; Allison, D; Yin, F
Abstract: Introduction/Objective: Russell bodies are nondegradable, condensed immunoglobulins accumulated in the overstimulated plasma cells, and the plasma cells filled with Russell bodies are called Mott cells. Russell body gastroenteritis is a rare entity that is mainly occurs in stomach and is associated with Helicobacter pylori infection. However, Russell body duodenitis is very rarely seen, so far only about four cases have been reported. Here we report a case of Russell body duodenitis within concurrent large duodenal adenoma with high-grade dysplasia in a 66- year old female. Methods: Formalin fixed, paraffin embedded tissue was examined stained with H&E and PAS-Alcian blue stain. Immunohistochemical stains (IHC) with appropriate controls were performed with the following antibodies: H. pylori, CD138, kappa and lambda light chains. Results: A 66-year old female had symptoms of difficult swallowing and decreased food intake. Upper GI endoscopy was performed to reveal a 7 cm multilobulated mass at the junction of the duodenal bulb and second portion of the duodenum, which involved the ampullary orifice. A biopsy for the mass showed a duodenal adenoma with high grade dysplasia. Numerous Mott cells were diffusely distributed within the lamina propria that was characterized by bright eosinophilic cytoplasmic globules with eccentric nuclei. The Mott cells were confirmed by IHC stains with positive CD138, PAS-Alcian blue, and polytypic expression of kappa and lambda light chains. The Helicobacter pylori immunostain was negative. Conclusion: Although the etiology is unknown, most of the Russell body gastroenteritis are seen in benign conditions. It is mainly found in stomach associated with Helicobacter pylori infection. To our knowledge, this is the first reported case of Russell body duodenitis with concurrent duodenal adenoma with high-grade dysplasia. Further studies should be conducted on Russell bodies associated with high-grade dysplasia or carcinoma in gastrointestinal tract.